ANALISIS MANAJEMEN PERGUDANGAN PADA GUDANG VMI (VENDOR MANAGED INVENTORY) DAN NON-VMI INDUSTRI ELEKTRONIK - Lufika, Raihan Dara; Izzaty, Nur; Suhendrianto, Suhendrianto; Arifin, Riski; Hamidah, Siti (Universitas Putera Batam, 2023)
The rapid development of industry in the modern era has resulted in increasingly fierce competition between manufacturing and service companies, encouraging companies to compete to provide superiority to consumers. A warehouse is one part that has a vital role in ensuring the smooth running of production activities. The purpose of the warehouse in this research object is as a place to receive raw materials, WIP (Work In Process) and finished goods from manufacturers, maintain stock accuracy based on planning, maintain good quality and control stock properly for export. The object observed is warehousing management in Vendor Managed Inventory (VMI) and Non-VMI warehouses. The problem that occurs is that the material is not placed in its place due to the addition of several new models. The results of the observations were analyzed using a tree diagram. Analysis of the root causes of the problem using a tree diagram obtained four main factors causing the problem, namely humans, SOPs, materials and the environment. The root causes of the four factors are the lack of communication and information between staff, the staff having multiple jobs, so the focus is divided, the flow of goods in and out does not follow the FIFO rules, the absence of temporary storage areas, not an optimal use of the warehouse and the addition of new models, causing the need for there is an improvement in the layout of the Non-VMI warehouse.